Selecting for three copepods—feeding of sprat and herring in the Baltic Sea. (2nd February 2018) - Ojaveer, Henn; Lankov, Ain; Raid, Tiit; Põllumäe, Arno; Klais, Riina
Abstract: Predator–prey interactions are a primary structuring force in marine foodwebs and they play an important role in the dynamics of both marine fish populations and their prey. We investigated the individual and spatial patterns in the feeding of two dominant zooplanktivorous clupeids—herring Clupea harengus membras and sprat Sprattus sprattus —in the Baltic Sea in summer, by means of a taxonomic analysis of stomach content. Both species consumed predominantly the small-sized copepods ( Temora longicornis, Eurytemora affinis, and Acartia spp.). E. affinis and T. longicornis were generally positively selected by both species. Centropages hamatus was selected only by sprat. With the exception of Pleopis / Podon spp. in the case of small sprat, the remaining prey, i.e. the zooplankton taxa that were found in fish stomachs, were consumed at similar proportions as they occurred in zooplankton. Stomach fullness of fish increased with the increasing proportions of prey in the zooplankton community. The share of empty stomachs was lower for sprat, and among smaller fish in both species. Pairwise dietary overlap between fish decreased when zooplankton diversity increased. Dietary overlap was also lowest among the individuals of sprat, probably due to the wider diet spectrum and diversity of stomach content compared to herring. Our results point to high interspecific competition, where sprat seems to be more successful than herring in finding and consuming prey, and therefore may have an advantage over herring when the zooplankton community is dominated by small-sized taxa.